Life history traits modulate the influence of environmental stressors on biodiversity: The case of fireflies, climate and artificial light at night. (14th June 2022) - Khattar, Gabriel; Vaz, Stephanie; Braga, Pedro Henrique Pereira; Macedo, Margarete; Silveira, Luiz Felipe Lima da
Abstract: Aim: Artificial light at night (ALAN) is an unprecedented stressor recently introduced in the abiotic milieu of natural landscapes. As such, understanding how ALAN and other natural stressors act in concert to shape the spatial distribution of biodiversity is a core goal in conservation ecology. Here, we aim at understanding how ALAN and climate interact with life history traits and courtship signalling systems to dictate the composition of firefly communities in a global biodiversity hotspot. Location: An extensive elevational gradient in the Atlantic rain forest (Brazil) currently known as the hottest hotspot of fireflies on Earth. Methods: We used multivariate species distribution models to understand how species traits and courtship signalling systems interact with climate and ALAN to determine species abundance within firefly communities. We also investigated how species‐specific responses to climate and ALAN scale up to determine compositional changes in firefly communities along the elevational gradient. Results: We found that climate shapes communities by filtering species according to their body size and trophic position. ALAN dictates the dominant courtship signalling system within communities by affecting the abundance of species that use bioluminescence or a combination of bioluminescence and pheromones in courtship. We also found that associations between beta‐diversity and ALAN were non‐stationary, being higher in regions under low levels of light pollution. This suggests that even incipient increases in ALAN within protected areas can yield fast changes in the composition of firefly communities. Main Conclusions: Firefly responses to climate and ALAN are modulated by traits associated with different facets of their life histories. Given the alarming changes in both stressors predicted for the foreseeable future, our findings indicate that firefly communities are vulnerable to compositional changes even within protected areas.